Study of Indonesia’s Solar Energy Implementation Using Identification of Potency, Policies, and Cost-Benefit Analysis - Anggoro, Mochammad Donny; Siregar, Diana; Ninggar, Regina; Wicaksono, Satriyo; Lee, Soo Hee (Journal of Earth Energy Engineering, 2021)
The solar PV systems are semiconductor devices that precisely convert sunlight into electricity, through the transfer of electrons. They provide several advantages, such as high modularity, zero noise, and adequate availability of solar resources in Indonesia. Therefore, this study aims to determine the potency, policy perspective, and Cost-Benefit Analysis (CBA) of the solar energy implementation for electricity generation. A statistical analysis was used for measuring potency, as well as reviewing opportunistic policies and barriers. A review of some CBA-based journals was also carried out, to determine that the development of solar power electricity had more benefit than fossil fuels and LCOE (Levelized Cost Of Electricity). The results of the 10-days average value calculation in 2019 were 388-563 W/m2, with the maximum values at 1137-1604 W/m2. Meanwhile the analysis of the maximum hourly averages for Western, Central, and Eastern Indonesia were 570-719, 634-758, and 559-627 W/m2 at 11.00-12.00 WIB, 11.00-13.00 WITA, and 12.00-13.00 WIT, respectively. The potency of solar radiation intensity in Indonesia was averagely 150-750 W/m2, as the highest values were found in East Nusa Tenggara, Maluku, and Merauke.